The relationship between atherogenic index and coronary collateral circulation - Aydın, Cihan; Abanoz, Mustafa (Journal of Surgery and Medicine, 2021)
Background/Aim: The atherogenic index of plasma (AIP) is a simple and useful biomarker that can predict plasma atherogenicity and coronary artery disease (CAD). Previous studies showed a relationship between AIP with CAD. Therefore, we researched the relationship between the AIP and coronary collateral circulation (CCC) in patients with chronic coronary total occlusion (CTO). Methods: Three hundred and twenty patients who underwent coronary angiography with the diagnosis of stable or unstable angina pectoris between 2015 and 2019 and who had CTO in at least one coronary artery were included in this retrospective study. The AIP was calculated as the logarithm of [Triglyceride (mg/dL) / high-density lipoprotein cholesterol (mg/dL)]. CCC was graded per the Rentrop grading system in patients with CTO after coronary angiography. Rentrop grades were as follows: 0-1: Low-grade (Group 1) CCC, 2-3: High-grade CCC (Group 2). Results: There were 170 and 150 patients in Groups 1 and 2, respectively, with the mean ages of 63.5 (9.5) years and 61.1 (10.1) years. Mean body mass index, left ventricular ejection fraction, the rate of hypertension, and smoking were similar between the two groups. The rate of diabetes mellitus (DM) was higher in Group 1 (P=0.006). Multivariate analysis showed that AIP (OR: 4.357, CI 95%: 2.741-6.335, P<0.001) and DM (OR: 0.893, CI 95%: 0.826-0.966, P=0.015) were independent predictors of poor CCC. Conclusion: In our study, we found that a high AIP is related to poor coronary collateral circulation.